Disruption of testicular histoarchitecture and plasma hormone concentrations due to heat stress in donkeys - Akhtar, Muhammad Faheem; Ahmad, Ejaz; Swelum, Ayman Abdel-Aziz; Ma, Qingshan; Wang, Changfa (Frontiers in Veterinary Science, 2026)
To maximize reproductive performance in farm animals, they must be protected from all kinds of stress, including heat stress (HS). Stress affects reproductive efficiency and the normal functioning of the hypothalamic–pituitary–gonadal (HPG) axis. The current study aimed to elucidate the effects of heat stress on reproductive efficiency in donkeys, including testicular histoarchitecture, stages of spermatogenesis, and variations in the plasma concentrations of testosterone, inhibin A, inhibin B, and luteinizing hormone (LH). A total of 30 Dezhou donkeys (Sanfen breed) were equally divided into two groups: Group A (n = 15) and Group B (n = 15). The animals in Group A were kept in an environmentally controlled shed where the temperature was maintained at 25 °C, while the animals in Group B were exposed to natural sunlight and kept in a barn during June, July, and August, when the average daily temperature ranged between 31 and 34 °C. Histological analysis revealed that HS decreased the seminiferous tubule diameter (STD), the number of spermatogonia, the number of seminiferous tubules (STs) per field, the number of spermatocytes, and the number of round and elongated spermatids. The diameter of the seminiferous tubules (STs) and epithelial height (EH) were positively correlated in June and August. In addition, STD, luminal tubular diameter (LTD), and the number of spermatocytes and round spermatids were positively correlated. In summary, we concluded that short-term heat stress reduces germ cells, spermatogenesis, and the number of spermatocytes and spermatids. It also causes alterations in testicular histoarchitecture without affecting the stages of spermatogenesis and decreases plasma concentrations of testosterone and luteinizing hormone. Moreover, inhibin B is the predominant form of circulating inhibin in donkeys.